Targeting NLRP3 Inflammasome in Translational Treatment of Nervous System Diseases: An Update - Yu, Qingying; Zhao, Tingting; Liu, Molin; Cao, Duo; Li, Jiaxin; Li, Yanling; Xia, Mengyao; Wang, Xiaoyu; Zheng, Tingting; Liu, Chuanguo; Mu, Xiangyu; Sun, Peng (Frontiers in Pharmacology, 2021)
Inflammation is a defensive response induced by dangerous stimuli. With the extensive and in-depth research on inflammation in the nervous system, inflammation plays an important role in the occurrence and development of a variety of neurological diseases. Inflammasome is a type of pattern recognition receptor, a cytoplasmic polyprotein complex composed of members of the Nod-like receptor (NLR) family and members of the pyrin and HIN domain (PYHIN) family, which can be affected by a variety of pathogen-related molecular patterns or damage-related molecular patterns are activated.Inflammasome activation is the activation of inflammation-related cysteine aspartate specific protease (caspase), interleukin-1β (IL-1β) and interleukin-18 (IL-18) and other inflammatory factors in the maturation process, and induce cell pyrolysis, playing an important role in coordinating the process of fighting pathogen infection and physiological disorders. As one of the research hotspots in the field of medical research in recent years, activated NLRP3 inflammasome can regulate the inflammatory response and the functions of related immune cells by controlling the maturation and secretion of a variety of pro-inflammatory cytokines. It plays an important role in natural immunity and acquired immune response.The NLRP3 inflammasome, as a signal receptor, regulates and secretes various major pro-inflammatory cytokines. NLRP3 inflammasome can be activated by a variety of stimuli, including microbial components and endogenous molecules. After activation, it can lead to the activation of inflammatory response and participate in the occurrence and development of a variety of neurological diseases.This article reviews the structure of NLRP3 inflammasome, it’s role in neurological diseases and related regulatory mechanisms, which providing references for future research in this field.